Essays on financial transaction taxes: Impact on trading volume, market composition and liquidity - Patrick Thöni (University of Copenhagen, Department of Economics, 2022)
Financial Markets have undoubtedly played a crucial role in the economic development and technological growth the world has experienced over the last century. The availability of liquid markets greatly facilitates the opportunities of raising capital and risk sharing, allowing the financing of large-scale real enterprises. Additionally, it enables savers to increase their returns while diversifying their risk. On the other hand, liquid markets also allow for speculative trading, which ultimately can lead to a misallocation of resources. This fundamental trade-off is what lies at the core of the original idea of a financial transaction tax (FTT). While proponents of FTTs highlight their potential to curb speculation driven by short term incentives, opponents argue that it would harm market quality by decreasing overall liquidity, interfering with price discovery and raising the cost of capital. This thesis furthers the existing body of work on this key tension surrounding FTTs from a financial microstructure perspective. By means of both theoretical and empirical analysis, the three self-contained chapters presented in this dissertation investigate the impact of FTTs on trading volume and migration, trader composition and ultimately market quality.
Keywords: 330